Femtosecond photoexcitation dynamics inside a quantum solvent - Bernhard Thaler; Sascha Ranftl; Pascal Heim; Stefan Cesnik; Leonhard Treiber; Ralf Meyer; Andreas W. Hauser; Wolfgang E. Ernst; Markus Koch (Nature Communications, 2018)
Femtosecond laser spectroscopy has contributed to our understanding of structure and function of matter. Here, the authors explore the applicability of superfluid helium nanodroplets as a sample preparation method that allows investigation of previously inaccessible classes of tailor-made or fragile molecular systems.